Structured porous surface for drag reduction and wake attenuation of cylinder flow. (1st March 2022) - Xu, Zhihan; Chang, Xu; Yu, Haiyang; Chen, Wen-Li; Gao, Donglai
Abstract: In the current study, a new passive flow control strategy characterized by 3D printing structured porous surface was introduced and experimentally investigated to manipulate the dynamic wake evolution and flow characteristics around a circular cylinder at a Reynolds number of 2.02 × 10 4 . With the 3D printing structured porous surface, parts of the incoming flow could go through the cylinder and communicate with the wake flow spontaneously. As a result, the vortex shedding was suppressed and the drag was reduced. From POD analysis results, we observed shifted modes and decreased vorticity distribution, indicating that the periodic vortex shedding process was weakened. This was also verified by the analysis of dynamic wake evolution and by the power spectrum analysis. In addition, experimental results showed that the time-averaged turbulent kinetic energy (TKE) and the Reynolds shear stress (RSS) distributions were restrained in the wake of the porous cylinder. Moreover, the mean estimated drag coefficients witnessed a significant decrease up to 49.47%. Highlights: The flow around a cylinder is modified via structured porous surface. The porous cylinder stabilizes the dynamic wake and alleviate the unsteady vortex shedding from the cylinder. The mean estimated drag coefficient is estimated to be decreased up to 49.47%.